Urban development and planning: An introduction - Pattanaik, Bikram keshari (London Routledge, 2025)
This book details the most contemporary concerns related to urban development, governance, and planning, as well as the challenges to urban administration. It analyses the policies and programmes adopted by both high-income and lower-middle-income countries to achieve sustainable urbanization and their application and treatment to help students get a holistic, practical perspective of the issues at hand. This volume elucidates urban development theories and approaches.